1997
DOI: 10.1017/s0022215100136631
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic rhinoscopy in lepromatous leprosy

Abstract: Ten patients with lepromatous leprosy have been studied to detect intranasal pathology by conventional naked eye rhinoscopy and also by use of the surgical microscope. The comparison of both methods reveals that microscopic rhinoscopy is superior in providing more accurate details of intranasal lesions in leprosy and biopsy can be taken in a precise manner from accurate and representative sites. Use of the microscope with adequate exposure and bright illumination provides precise details of lesions and an oppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…We would like to point out that it is possible to suspect of a case of Leprosy only through the clinical history associated with the ENT examination, especially when we perform it with rigid or flexible endoscope, a fact also observed by the authors Soni (1997) 21 and Fokkens et al (1998) 22 . The exam enables the identification of mucosa lesions that are not observed when we use only nasal speculum in the anterior rhinoscopy, such as hansenomas and vasculitis (Photo 3).…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…We would like to point out that it is possible to suspect of a case of Leprosy only through the clinical history associated with the ENT examination, especially when we perform it with rigid or flexible endoscope, a fact also observed by the authors Soni (1997) 21 and Fokkens et al (1998) 22 . The exam enables the identification of mucosa lesions that are not observed when we use only nasal speculum in the anterior rhinoscopy, such as hansenomas and vasculitis (Photo 3).…”
Section: Discussionmentioning
confidence: 67%
“…In addition to infiltration and presence of blood on the mucosa of nasal cavities, we could identify the presence of crusts (Photos 1, 2 and 4) at the nasal endoscopy of 54 patients, representing 31.2% of the 173; it was also a frequent finding in the study by Barton (1974) 5 , who found it in 74% of the 77 studied patients, by Fokkens et al (1998) 22 , who found 62% among the 40 studied patients, and by Srinivasan Photo 1. LL presentation with septal anterior-inferior damage, presence of vasculitis, dryness, infiltration, mucosa hyperemia, crusts and blood spots.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…5 Nasal and paranasal lesions occur in the early stages of leprosy, and as many as 94 per cent of patients develop nasal symptoms. 2 The nasal mucosa is a very important initial focus of M leprae infection. 2 The nasal mucosa is a very important initial focus of M leprae infection.…”
Section: Introductionmentioning
confidence: 99%
“…2 The nasal mucosa is a very important initial focus of M leprae infection. 2 Previous studies of sinonasal morbidity in leprosy have usually targeted untreated leprosy patients. 7 Chronic granulomatous infection finally causes septal perforation, saddle nose deformity and secondary atrophic rhinitis.…”
Section: Introductionmentioning
confidence: 99%